Critical care nursing role in low and lower middle-income settings: a scoping review. Issue 1 (4th January 2022) - Macey, Andy; O'Reilly, Gerard; Williams, Ged; Cameron, Peter
Abstract : Objectives: A scoping review was conducted to answer the question: How is critical care nursing (CCN) performed in low-income countries and lower middle-income countries (LICs/LMICs)? Design: Scoping review guided by the JBI Manual for Evidence Synthesis. Data sources: Six electronic databases and five web-based resources were systematically searched to identify relevant literature published between 2010 and April 2021. Review methods: The search results received two-stage screening: (1) title and abstract (2) full-text screening. For sources of evidence to progress, agreement needed to be reached by two reviewers. Data were extracted and cross-checked. Data were analysed, sorted by themes and mapped to region and country. Results: Literature was reported across five georegions. Nurses with a range formal and informal training were identified as providing critical care. Availability of staff was frequently reported as a problem. No reports provided a comprehensive description of CCN in LICs/LMICs. However, a variety of nursing practices and non-clinical responsibilities were highlighted. Availability of equipment to fulfil the nursing role was widely discussed. Perceptions of inadequate resourcing were common. Undergraduate and postgraduate-level preparation was poorly described but frequently reported. The delivery of short format critical care courses was more fully described. There were reports of educational evaluation, especially regarding internationally supported initiatives. Conclusions: Despite commonalities, CCN is unique to regional and socioeconomic contexts. Nurses work within a complex team, yet the structure and skill levels of such teams will vary according to patient population, resources and treatments available. Therefore, a universal definition of the CCN role in LIC/LMIC health systems is likely unhelpful. Research to elucidate current assets, capacity and needs of nurses providing critical care in specific LIC/LMIC contexts is needed. Outputs from such research would be invaluable in supporting contextually appropriate capacity development programmes.